(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2023)
Organizational commitment is the willingness of employees to stay in the company and give the best they can for the company. The purpose of this study was to determine how the influence of transformational leadership on job satisfaction and organizational commitment. This research was conducted at BPR Lestari Sesetan Branch. Samples taken were 74 respondents. Data collection techniques are observation, interviews, documentation, literature and questionnaires. Analytical methods used are validity, reliability, path analysis and Sobel test. The test results show that transformational leadership has a positive and significant effect on organizational commitment at BPR Lestari Sesetan Branch in Denpasar City. Transformational leadership has a positive and significant effect on job satisfaction at BPR Lestari Sesetan Branch in Denpasar City. Job satisfaction has a positive and significant effect on organizational commitment at BPR Lestari Sesetan Branch in Denpasar City. Job satisfaction is able to mediate the effect of transformational leadership on organizational commitment at BPR Lestari Sesetan Branch in Denpasar City. Suggestions for this research are expected that the leadership can motivate and inspire subordinates so that they can become role models for their subordinates.